FUNGSI TUTUR KALIMAT TANYA BAHASA INDONESIA - Lindawati Lindawati (LITERA, 2012)
This study examines interrogative sentences in Indonesian by focusing on speechfunctions. The data were interrogative sentences in Indonesian nowadays used incommunication among ethnic groups. It employed the pragmatic approach stating thatwhen one is saying a sentence at the same time s/he is performing an action called aspeech act. An interrogative sentence, which is basically used to ask a question aboutsomething, can also be used to express a variety of speech acts. The findings show that there are four speech acts expressed by interrogative sentences, namely representative, directive, comissive, and expressive acts. Interrogative sentences are sometimes used to express indirect speech acts to maintain politeness (to soften the tone) or to express something firmly, rudely, and even impolitely.